REORIENTATION OF PUBLIC SERVICES IN INDONESIA: A STUDY OF TRANSCENDENTAL DIMENSIONS OF LAW - Mochamad Nuruz Zaman; Ryan Saputra Alam (Scientium Law Review (SLR), 2022)
Public service is one of the means to build public trust to realize national development goals. However, the report received by the Ombudsman of the Republic of Indonesia shows the implementation of public services has not been to the needs and changes in various community, national, and state life. Concerns about the inefficiency of public services and many rules and standard operating procedures indicate the need to reorientate public services in Indonesia. Based on normative juridical studies, two conclusions were produced. First, so far, public services in Indonesia are only for the fulfillment of certainty of laws and regulations, which seem to be just fulfilling formal justice. Second, it is necessary to reorient public services, namely public services that explore transcendental dimension laws, so that the general knowledge offered by the state to its people can exceed the limitations of written rules by giving the meaning of every existing law by not going out of laws born of ideal nature, which is true. This can be conducted by synthesizing a priori knowledge with apository knowledge. Inside a priori of public service, the implementation must show on the condition of a good experience while remaining based on rational thinking.